3,396
pages

The ${\displaystyle \operatorname{rfg}(x)}$ function is a function defined by the following:

${\displaystyle \operatorname{rfg}(x) = x^2(x(x + 1))(x(x + 2))(x(x + 3))...(x(2x))}$

Let's plug in some values of x and see what we get:

${\displaystyle \operatorname{rfg}(0) = 0}$

${\displaystyle \operatorname{rfg}(1) = 2}$

${\displaystyle \operatorname{rfg}(2) = 192}$

${\displaystyle \operatorname{rfg}(3) = 21960}$

${\displaystyle \operatorname{rfg}(4) = 6881290}$

You can see how quickly this grows. Now we can do the same thing for ${\displaystyle i}$:

${\displaystyle \operatorname{rfg}(xi) = i(\operatorname{rfg}(x))}$

${\displaystyle \operatorname{rfg}(x + yi) = (\operatorname{rfg}(x) + \operatorname{rfg}(y)) + (x + y)i}$

${\displaystyle \operatorname{rfg}(x - yi) = (\operatorname{rfg}(x) - \operatorname{rfg}(y)) - (x + y)i}$

The ${\displaystyle \operatorname{rfg}(x)}$ function can also have as many parameters as you want because:

${\displaystyle \operatorname{rfg}(x, y) = \operatorname{rfg}(x)(\operatorname{rfg}(y))}$

I want you to think about what this might be useful for. If it is useful, then explain why.